2012
DOI: 10.1007/s00277-012-1631-y
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli and Klebsiella pneumoniae bacteremia in patients with neutropenic fever: factors associated with extended-spectrum β-lactamase production and its impact on outcome

Abstract: Escherichia coli and Klebsiella pneumoniae are main pathogens in neutropenic fever even if the proportion of Gram-positive cocci is increasing. Extended-spectrum β-lactamases (ESBL)-producing organisms are an emerging problem in nosocomial infection. Nevertheless, until now, information about risk factors for the acquisition and clinical outcomes of bacteremia due to ESBL-producing organisms is limited in neutropenic patients. From medical records collected between January 2007 and December 2008, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 38 publications
5
43
0
4
Order By: Relevance
“…Epidemiological studies have shown it to be the second or third leading cause of bacteremia in such patients [23][24][25]. The reported risk of mortality from K. pneumoniae bacteremia is 18-30 %, and is even higher in patients infected with multidrug-resistant strains [25][26][27][28].…”
Section: Discussionmentioning
confidence: 98%
“…Epidemiological studies have shown it to be the second or third leading cause of bacteremia in such patients [23][24][25]. The reported risk of mortality from K. pneumoniae bacteremia is 18-30 %, and is even higher in patients infected with multidrug-resistant strains [25][26][27][28].…”
Section: Discussionmentioning
confidence: 98%
“…37,[49][50][51] For example, ESBL-producing strains accounted for the 26% of all the E. coli and K. pneumoniae isolates in neutropenic patients in a South Korean study and for approximately 40% in Italian cohorts 36,43,49,52 Carbapenem-resistant gram-negative bacteria Carbapenem-resistance among GN bacteria is rising worldwide, different resistance mechanisms underlie non-susceptibility to this class of b-lactams, and K. pneumoniae, E. coli, P. aeruginosa and A. baumannii are the most affected species. 45,53 In consequence, in many countries, also cancer patients develop carbapenemresistant infections, as demonstrated by a retrospective survey performed in 52 transplant centers in Italy.…”
Section: Esbl-producing Enterobacteriaceaementioning
confidence: 99%
“…loodstream infection (BSI) due to extended-spectrum-␤-lactamases (ESBLs) is increasingly being identified among patients with hematological malignancies (1)(2)(3)(4)(5). This is of special concern because a delay in initiating adequate antibiotic therapy may impair their outcomes (1,6).…”
mentioning
confidence: 99%